Determinants of the recommended phase 2 dose of molecular targeted agents. Issue 8 (9th February 2017) - Hansen, Aaron R.; Cook, Natalie; Amir, Eitan; Siu, Lillian L.; Abdul Razak, Albiruni Ryan
Abstract : BACKGROUND: The recommended phase 2 dose (RP2D) of anticancer agents is determined traditionally by dose‐limiting toxicities. Nontoxicity or biological endpoints such as pharmacokinetics, pharmacodynamics, and efficacy can also be used to identify RP2D, which may be relevant to molecularly targeted agents (MTAs). METHODS: A systematic review identified all monotherapy phase 1 studies of MTAs in solid tumors published between 2001 and 2013. Dose, dosing schedule, and determinants of RP2D were collected from each study. A supplementary search of the US Food and Drug Administration (FDA) website identified the licensed dose for drugs with regulatory approval. Logistic regression was used to explore predictors for the RP2D being consistent with the final approved dose. RESULTS: The search identified 4175 records, of which 250 studies evaluating 181 individual MTAs were included. Of these MTAs, 161 (64%) determined an RP2D. Fifty‐two trials (32%), used toxicity alone to specify an RP2D. The remaining trials used a nonclassical approach with either multiple endpoints that included toxicity (n = 87, 54%), multiple nontoxicity endpoints (n = 12, 7%), or a single nontoxicity endpoint (n = 10, 6%). Twenty‐nine (16%) MTAs were approved by the FDA for solid tumor indications. The use of nonclassical definitions compared with toxicity alone was significantly associated with higher likelihood of FDA approval (odds ratio, 5.03; 95% confidence interval, 1.11‐22.73; P = .036). CONCLUSIONS: In the past decade, there has been a dominance of a nonclassical approach using multiple endpoints with or without toxicity or single nontoxicity endpoints to define RPTD in MTA monotherapy phase 1 trials. Nonclassically defined RP2Ds for MTAs appear to be associated with a higher rate of FDA drug approval. Cancer 2017;123:1409–1415. © 2016 American Cancer Society . Abstract : In the era of molecular targeted agents (MTAs), it is unclear whether toxicity is the optimal method for identifying a recommended phase 2 dose (RP2D). Phase 1 trials of monotherapy MTAs more frequently use nontoxicity parameters to define RP2D, and the use of such endpoints is significantly associated with a higher likelihood of regulatory approval for MTAs. See also pages 1298‐300.